(11x -1) /(2x+3)=2...solve this
Answers
Answered by
2
Answer:
this is the answer for your question
Attachments:
![](https://hi-static.z-dn.net/files/d4e/1da4dbb659890e5dab87e6aa28fd2638.jpg)
Answered by
0
Answer: x = 1
Step-by-step explanation:
(2x + 3)[(11x - 1)/(2x + 3)] = 2(2x + 3)
11x - 1 = 4x + 6
11x - 1 + 1 = 4x + 6 + 1
11x = 4x + 7
11x - 4x = 4x + 7 - 4x
7x = 7
7x/7 = 7/7
x = 1
Similar questions
English,
2 months ago
Chemistry,
4 months ago
Physics,
4 months ago
Social Sciences,
10 months ago
Math,
10 months ago